MODEL PjBL DAN KETERAMPILAN BERPIKIR KRITIS PADA ERA DIGITAL: UPAYA MENINGKATKAN KEMAMPUAN MENULIS ESAI PESERTA DIDIK - Retno Satuti; Retno Winarni; Eka Budhi Santosa (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Mastery of essay writing constitutes a critical component in the development of higher-order thinking skills among elementary school students in the digital age. The observed difficulties of students in organizing ideas and constructing logical arguments highlight the pressing need for innovative instructional approaches that promote active participation and reflective reasoning. The study employs a quasi-experimental design, 60 fifth-grade students from the Gajah Mada Giriwoyo Cluster. The primary instrument used for data collection was an essay assessment tool, developed based on coherence, cohesion, sentence structure, and idea development criteria. Data analysis procedures included independent t-tests, two-way ANOVA tests, and N-Gain index calculations to evaluate the magnitude of learning improvement. The findings demonstrate a statistically significant distinction between the experimental and control groups, indicated by a p-value of 0.0208 and an average N-Gain of 0.24 for the experimental group. Moreover, critical thinking proficiency among students was found to exert a substantial effect on their progress in essay writing skills. Based on these results, the study recommends that educators incorporate project-based methodologies as a strategy to enrich literacy instruction practices in elementary education settings.